Eco-Theology: Purification of Respect Against Du'a Ngga'e Ende-Lio Tribe - Nara, Marianus Angi; Sudhiarsa, Raymundus I Made; Yuniarto, Petrus (International Journal Ethnic, Racial and Cultural Heritage, 2024)
Each culture has its unique approach to understanding the concept of safety, and the Ende-Lio culture on Flores Island, Indonesia, is no exception. In the Ende-Lio culture, the concept of salvation is known as "Du'a Ngga'e," which forms the basis of understanding life's purpose, balance with nature, and relationship with the universe. This paper focuses on understanding Du'a Ngga'e as a theological concept that emphasizes the importance of maintaining balance in human interaction with nature, gods, and ancestral spirits. This concept represents the belief that good actions and righteous ethics will ensure the safety of individuals and communities in this world and towards life after death. Therefore, Ndua Ngga'e emphasizes caring for nature, maintaining a harmonious relationship with the universe, and living with high ethics. This study illustrates how Ende-Lio cultures understand and integrate the concept of ecological theology in their daily lives. The concept of D'ua Ngga'e inspires positive action in safeguarding nature and promoting a healthy relationship between humans and the universe.